Quantitative subcellular acyl-CoA analysis reveals distinct nuclear metabolism and isoleucine-dependent histone propionylation - Trefely, Sophie; Huber, Katharina; Liu, Joyce; Noji, Michael; Stransky, Stephanie; Singh, Jay; Doan, Mary T; Lovell, Claudia D; von Krusenstiern, Eliana; Jiang, Helen; Bostwick, Anna; Pepper, Hannah L; et al. (Molecular cell, 2022)
Quantitative subcellular metabolomic measurements can explain the roles of metabolites in cellular processes but are subject to multiple confounding factors. We developed stable isotope labeling of essential nutrients in cell culture-subcellular fractionation (SILEC-SF), which uses isotope-labeled internal standard controls that are present throughout fractionation and processing to quantify acyl-coenzyme A (acyl-CoA) thioesters in subcellular compartments by liquid chromatography-mass spectrometry. We tested SILEC-SF in a range of sample types and examined the compartmentalized responses to oxygen tension, cellular differentiation, and nutrient availability. Application of SILEC-SF to the challenging analysis of the nuclear compartment revealed a nuclear acyl-CoA profile distinct from that of the cytosol, with notable nuclear enrichment of propionyl-CoA. Using isotope tracing, we identified the branched chain amino acid isoleucine as a major metabolic source of nuclear propionyl-CoA and histone propionylation, thus revealing a new mechanism of crosstalk between metabolism and the epigenome.